2022
DOI: 10.3389/fvets.2022.958724
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the immunomodulatory properties of equine BM-MSCs culture expanded in autologous platelet lysate, pooled platelet lysate, equine serum and fetal bovine serum supplemented culture media

Abstract: Joint injury often leads to cartilage damage and posttraumatic inflammation, which drives continued extracellular matrix degradation culminating in osteoarthritis. Mesenchymal stem cells (MSCs) have been proposed as a biotherapeutic to modulate inflammation within the joint. However, concerns have been raised regarding the immunogenicity of MSCs cultured in traditional fetal bovine serum (FBS) containing media, and the potential of xenogenic antigens to activate the immune system causing rejection and destruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
1
2
0
Order By: Relevance
“…Finally, the presence of these cytokines may be the result of molecular retention on the MSC surface that PBS washes did not succeed in eliminating. This hypothesis was also mentioned in a recent study that found higher levels of IL-1β in CMs primed with this cytokine (Even et al, 2022). These three hypotheses are not mutually exclusive and may explain our results.…”
Section: Figure 10supporting
confidence: 85%
“…Finally, the presence of these cytokines may be the result of molecular retention on the MSC surface that PBS washes did not succeed in eliminating. This hypothesis was also mentioned in a recent study that found higher levels of IL-1β in CMs primed with this cytokine (Even et al, 2022). These three hypotheses are not mutually exclusive and may explain our results.…”
Section: Figure 10supporting
confidence: 85%
“…Interestingly, Even et al [ 47 ] mentioned the comparative results of equine serum (ES), A-PL, pooled PL, and FBS on the immunomodulatory properties of BM-MSCs. According to this study, ES enhanced the immunostimulatory properties of BM-MSCs, while A-PL increased the levels of platelet-derived and inherent growth factors in BM-MSCs [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Even et al [ 47 ] mentioned the comparative results of equine serum (ES), A-PL, pooled PL, and FBS on the immunomodulatory properties of BM-MSCs. According to this study, ES enhanced the immunostimulatory properties of BM-MSCs, while A-PL increased the levels of platelet-derived and inherent growth factors in BM-MSCs [ 47 ]. This study clearly supports our findings, as PL contains a wide variety of growth factors that not only promote MSC growth but also act as chemoattractants for in vivo stem cell growth.…”
Section: Discussionmentioning
confidence: 99%